2013
DOI: 10.1007/s11255-013-0522-z
|View full text |Cite
|
Sign up to set email alerts
|

Urine kidney injury molecule-1: a potential non-invasive biomarker for patients with renal cell carcinoma

Abstract: Objective To evaluate the use of urine KIM-1 as a biomarker for supporting a diagnosis of kidney cancers before operation. Methods A total of 19 patients were enrolled in the study based on preoperative imaging studies. Pre-operative and follow-up (1 month) uKIM-1 levels were measured and normalized with uCr levels and renal tumors were stained for KIM-1 using immunohistochemical techniques. Results The percentage of KIM-1 positive staining RCC cells ranged from 10 to 100% and the staining inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 25 publications
(35 reference statements)
1
32
2
6
Order By: Relevance
“…The poor expression of KIM-1 in chRCC concurred with other previous IHC results where the majority of chRCC were negative for KIM-1. However, our findings of KIM-1 expression in 80% of RO was certainly different to previous reports where RO were all negative for KIM-1 immunostaining (Han et al 2005;Zhang et al 2014) Urinary KIM-1 levels have also been closely associated with renal cancers, especially ccRCC and papillary RCC. In the first study, Han et al showed that in all 5 RCC patients with detectable prenephrectomy urinary KIM-1, there was either complete disappearance or marked reduction after nephrectomy.…”
Section: Leptin and Leptin Receptorcontrasting
confidence: 99%
See 4 more Smart Citations
“…The poor expression of KIM-1 in chRCC concurred with other previous IHC results where the majority of chRCC were negative for KIM-1. However, our findings of KIM-1 expression in 80% of RO was certainly different to previous reports where RO were all negative for KIM-1 immunostaining (Han et al 2005;Zhang et al 2014) Urinary KIM-1 levels have also been closely associated with renal cancers, especially ccRCC and papillary RCC. In the first study, Han et al showed that in all 5 RCC patients with detectable prenephrectomy urinary KIM-1, there was either complete disappearance or marked reduction after nephrectomy.…”
Section: Leptin and Leptin Receptorcontrasting
confidence: 99%
“…Previous reports have also showed strong expression of KIM-1 in ccRCC (Han et al 2005;Lin et al 2007;Zhang et al 2014). …”
Section: Leptin and Leptin Receptormentioning
confidence: 72%
See 3 more Smart Citations